KERAGAMAN GENETIK ANAKAN Shorea leprosula BERDASARKAN PENANDA MIKROSATELIT - Purnamila Sulistyawati; AYPBC Widyatmoko; ILG Nurtjahjaningsih (Jurnal Pemuliaan Tanaman Hutan, 2014)
Genetic diversity value of offspring might indicate a reproductive success in a forest. Aim in this study was to access genetic diversity values of offspring of Shorea leprosula from different forest types. Leaf samples were collected from six population i.e. a plantation from Carita, and five natural forests from Gunung Bunga A and B, SBK, ITCI and Gunung Lumut. Using four microsatellite markers, the results showed that SBK population maintained high value of genetic diversity. Values of expected heterozygosity (HE) ranged between 0.717 (Carita) and 0.836 (SBK). Values of coefficient inbreeding (F) were insignificant deviated from Hardy-Weinberg Equilibrium, but the value was significant in SBK population. PCA analysis demonstrated a cluster among Gunung Bunga A, SBK, ITCI, and Gunung Lumut. Amova showed that different province significantly contributed 1% to the value of genetic diversity of S. leprosula.